THE IMPACT OF TRAINING AND INCENTIVES ON ORGANIZATIONAL CREATIVITY: AN APPLIED STUDY ON A SAMPLE OF PRIVATE IRAQI BANKS - Shaher Rekan Radhi; Aysar Abduladheem Dakhyliy (International Journal of Artificial Intelligence for Digital Marketing, 2026)
Objective: The research paper examines organizational creativity and training and incentives in a sample of the Iraqi banks, which are privately owned. The study will evaluate the effectiveness of structured program of employee development and reward systems in enhancing creativity at the workplace. Method: The quantitative design was adopted with the help of the structured questionnaire that was sent to 248 employees of Al-Kindi Private Bank for Investment, Cihan Bank of Islamic Investment and Finance, and the Bank of Baghdad. The measure had three variables, namely training, incentives, and organizational creativity, which were measured on a five-point Likert scale. The SPSS 29 was used in conducting the statistical analysis, including reliability testing, correlation analysis, multiple regression and diagnostic tests.  Results: Findings indicated that training and incentives impact on organizational creativity in a significant and positive manner, albeit a little more so with training. The regression model defined 63.7 percent of the creativity variance and all diagnostic tests proved the validity of the model. The descriptive statistics showed that the employees had a high perception of the existing training and incentive practices. The research finds that innovation and flexibility can be improved by the private banks in Iraq through investment in specific training programs and equitable systems of incentives. Novelty: The results are of relevance to the literature as they present context-specific evidence in the Iraqi banking industry. The suggestions are to incorporate creativity-driven development in HR policies, use non-financial motivational instruments, and endorse a favorable organizational culture.